2004
DOI: 10.3766/jaaa.15.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Reception Thresholds for Sentences in Bilingual (Spanish/English) and Monolingual (English) Listeners

Abstract: Recent evidence on the perceptual performance of bilingual listeners suggests that a nonaudibility-based cost exists in processing a second language. That is, when compared to monolingual English speakers and early bilinguals, listeners who acquired English as a second language after puberty show reduced performance when listening to the second language in background noise, despite normal auditory thresholds. However, past studies have not controlled for the homogeneity of the bilingual participants used in au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
42
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 18 publications
10
42
1
3
Order By: Relevance
“…Previous research has shown that bilinguals may perform speech recognition tasks as equally well as their monolingual peers in quiet; degraded listening conditions, such as noise or reverberation, however, have been found to more adversely affect speech recognition performance in bilinguals than monolinguals despite normal auditory thresholds [31][32][33][34]. The current finding that monolinguals overall outperform bilinguals in the absence of noise has not been as widely reported in the literature.…”
Section: Discussioncontrasting
confidence: 47%
“…Previous research has shown that bilinguals may perform speech recognition tasks as equally well as their monolingual peers in quiet; degraded listening conditions, such as noise or reverberation, however, have been found to more adversely affect speech recognition performance in bilinguals than monolinguals despite normal auditory thresholds [31][32][33][34]. The current finding that monolinguals overall outperform bilinguals in the absence of noise has not been as widely reported in the literature.…”
Section: Discussioncontrasting
confidence: 47%
“…Two very clear conclusions emerge from these studies. Non-native listeners do indeed suffer more from increasing noise than natives when the task involves word or sentence processing in fixed or variable noise levels (Black and Hast, 1962;Gat and Keith, 1978;Florentine et al, 1984;Florentine, 1985;Buus et al, 1986;Mayo et al, 1997;Meador et al, 2000;van Wijngaarden et al, 2002;von Hapsburg et al, 2004;Cooke et al, 2008). However, for tasks which minimise or eliminate the possibility of using high-level linguistic information, noise has an equivalent overall effect on native and non-native listeners (Flege and Liu, 2001;Mackay et al, 2001a, b;Cutler et al, 2004;Rogers et al, 2006); even low-level predictability is better exploited by native listeners .…”
Section: Non-native Speech Perception Under Energetic Maskingmentioning
confidence: 99%
“…Indeed, several authors (von Hapsburg and Peña, 2002;von Hapsburg et al, 2004;Weiss & Dempsey, 2008) advocate a thorough description and control of several speaker variables that introduce heterogeneity in subject sample populations and have been shown to influence linguistic performance. However, in their own work, language proficiency is measured by selfassessment, which is an intrinsically subjective measure and may vary culturally (Hazan and Simpson, 2000).…”
Section: Listener Typementioning
confidence: 99%
See 1 more Smart Citation
“…The non-native speakers tested in the current study were late bilinguals, defined by L2 acquisition at or after 10 yrs of age (von Hapsburg et al, 2004). Von Hapsburg et al (2004) tested SRTs using the clinical version of the Hearing in Noise Test (HINT; Nilsson et al, 1994) in native monolingual English speakers and late bilinguals, whose L1 was Spanish and L2 was English. The non-native speakers in that study required an SNR up to 3.9 dB higher than the native speakers to achieve similar recognition on the HINT.…”
Section: Non-native Late Learnersmentioning
confidence: 99%